Factor (F)VIII/VIIa enhances global haemostatic function in the co‐presence of bypassing agents and FVIII among patients with haemophilia A with inhibitor. (2nd April 2018) - Nogami, Keiji; Matsumoto, Tomoko; Yada, Koji; Ogiwara, Kenichi; Furukawa, Shoko; Shida, Yasuaki; Takeyama, Masahiro; Shima, Midori
Summary: Bypassing therapy is essential for the haemostatic management of patients with haemophilia A with inhibitor (PWHA‐inh), but the therapeutic effects are inconsistent. We previously reported that activated prothrombin complex concentrates (aPCC) activated factor (F)VIII in vitro, and was mediated mainly by the activated FVII (FVIIa) contained in aPCC. We have extended those studies to assess global coagulation in whole blood from 18 PWHA‐inh in the co‐presence of aPCC and FVIII using Ca 2+ ‐triggered rotational thromboelastometry. The clot times (CTs) in the presence of both aPCC (0·05 iu/ml) and recombinant (r)FVIII (1 iu/ml) ex vivo were shortened compared to the aPCC alone ( P  <   0·01). These enhancing effects of rFVIII were observed, irrespective of recognizing inhibitor epitopes; however, the clot formation time and 'α'‐angle were not significantly different. In samples from 7 PWHA‐inh post‐infusion of aPCC (70‐80 iu/kg), only the CTs were shortened in the presence of rFVIII ex vivo compared to its absence ( P  <   0·05), indicating that the enhanced activity centred on the initiation phase of coagulation. Furthermore, experiments in the co‐presence of rFVIIa and rFVIII demonstrated that FVIII accelerated only the CTs. We concluded that FVIII/FVIIa‐related coagulation mechanism enhanced global haemostatic function by the co‐presence of bypassing agents and FVIII in PWHA‐inh.